The Potential of Oligochaeta as Intermediate Host of Myxosporea Parasite in Common Carp (Cyprinus carpio Linnaeus) - Hadiroseyani, Yani (Jurnal Akuakultur Indonesia, 2003)
Three genera of oligochaeta, i.e. Branchiura sowerbyi, Limnodrillus sp. and Lumbriculus sp. were fed on spores of Myxobolus artus before predated to juvenile of Cyprinus carpio. Spores of myxosporean were found on the fish, which get Limnodrillus. But those spores show different characters from spores of M. artus. Key words: Myxosporean, Myxobolus artus, oligochaeta, Branchiura sowerbyi, Limnodrillus, Lumbriculus, Cyprinus carpio   ABSTRAK Spora Myxobolus artus yang berasal dari ikan mas ditularkan kembali melalui rantai makanan kepada ikan mas berumur 50 hari. Inang antara yang digunakan adalah oligocheta jenis Branchiura sowerbyi, Limnodrillus sp. dan Lumbriculus sp.  Hasil percobaan menunjukkan bahwa ikan mas yang mendapat Limnodrillus terinfeksi oleh myxosporea yang berbeda dari M.artus. Kata kunci: Myxosporea, Myxobolus artus, oligochaeta, Branchiura sowerbyi, Limnodrillus, Lumbriculus, Cyprinus carpio